Response of Escherichia coli B/r to High Concentrations of Sucrose in a Nutrient Medium - Scheie, Paul O. (1972)
Escherichia coli B/r was subjected to sucrose concentrations up to 1 m in the presence of Nutrient Broth. Plasmolysis seldom was evident 2 min after this treatment. The subsequent response was characterized by transient decreases in optical density as well as changes in appearance as seen under phase optics. No transient effects were detected in the synthetic rates or in the division of the survivors.